Estimation of antibacterial activity of purified bioactive compounds separately and in combination with Chloramphenicol against Shiga toxin producing and Enterotoxigenic Escherichia coli - Biswas, Deboshree; Roymon, M G (Recent Research in Science and Technology, 2013)
The study was carried out in order to investigate potential antibacterial efficacy of p-Coumaroyl-glucoside + p-Coumaroylquinic acid, Ferulic acid and Steroidal sapogenin individually as well as in combination with Chloramphenicol against Shiga toxin producing and standard Enterotoxigenic E. coli strain. Estimation of antibacterial effect was carried out by well-diffusion method. Strongest inhibitory result was observed from p-Coumaroyl-glucoside + p-Coumaroylquinic acid with zone of inhibition of 23.3 ±0.6 mm for Shiga toxin producing E. coli and 24.0 ± 1.1mm for standard Enterotoxigenic E. coli strain. The zone of inhibition recognized from Ferulic acid was of 14.6± 2.4 mm and 12.0±0.0 mm respectively for Shiga toxin producing and Enterotoxigenic E. coli strain. From Steroidal sapogenin the recognized inhibitory zone diameter found in the two strains were of 16.6±0.6 mm and 12.0±1.1 mm. Combined administration of the bioactive compounds and Chloramphenicol strongest interaction was recognized with -Coumaroyl-glucoside + p-Coumaroylquinic acid and Steroidal sapogenin whereas neither synergism nor antagonism was recognized on combined administration of Ferulic acid and Chloramphenicol determined on the basis of enhancement of inhibitory zone diameter.